The multilingual mind: A modular processing perspective - Sharwood Smith, Michael, 1942- (New York, USA: Cambridge University Press, 2014)
"This book is the first detailed description of a particular theoretical framework for studying language development and language performance. The framework is called MOGUL (Modular On-line Growth and Use of Language). It has been the topic of numerous publications and presentations since the appearance of our 2004 keynote article in Bilingualism: Language & Cognition. MOGUL is not just about how a language grows in the individual child: it is about how the mind expands to accommodate more than one language both in childhood and later in life and how these various linguistic systems share space and interact"--
Machine generated contents note: 1. Introduction; Part I. The Framework: 2. The language module: architecture and representations; 3. Processing in the language module; 4. Growth of the language module: acquisition by processing; 5. Beyond the language module; Part II. Applying the Framework: 6. The bilingual mind introduced; 7. The growth of a second language; 8. Consciousness and attention; 9. The role of consciousness in language growth; 10. Issues in SLA revisited; 11. Conclusion; References.
Includes bibliographical references (pages 361-400) and index.
Keywords: Multilingualism; LANGUAGE ARTS & DISCIPLINES / Linguistics / General